Surface Modification of Ni-Ti Stents by Biodegradable Binary PVA/Propolis Electrospun Nano Fibers - Mutuk, Tugba; Gurbuz, Mevlut (Springer Heidelberg, 2023)
Ni-Ti stents are perceived as foreign substances in the body and cause damage to the cell wall. Therefore, binary PVA/Propolis (PVA/PP) biopolymer nanofibers were spun on commercial Ni-Ti stent surfaces with electrospinning method to overcome these problems. In this study, the spun coatings' suspension mixtures were prepared in different ratios as 10 wt% PVA-1 wt% PP, 10 wt% PVA-3 wt% PP, 10 wt% PVA-5 wt% PP. The successively fabricated nanofibers (< 100 nm) were characterized with a stereo microscope, SEM, FTIR, AFM, and TG, dissolution and antibacterial tests. From the results, the best-spun rates and spun amounts were determined as 10 wt% PVA-5 wt% PP composition. The fiber coatings well adhere to the Ni-Ti stent surface and form a fiber structure without gaps. PVA/PP decomposition temperature decreased compared to PVA with increasing propolis from TG analysis. The strong hydrogen bonds were formed between the PVA and PP from FTIR analyses. The antibacterial effect against Escherichia Coli. shown for PVA/PP composition. In bioactivity test, the higher pH change (6.98 to 7.65) and mass change (0.0165 to 0.0565 g) were observed for 10 wt% PVA-5 wt% PP coated Ni-Ti stent in Ringer's solution depends on the immersion day. 10PVA-5PP coated sample had also been found that dissolves in artificial body fluid and more nanofiber structure. More nanofibers (diameter 30-35 nm) and less beadless morphology were fabricated for 10PVA-5PP. The higher surface roughness values (Ra: 68.95 nm) were observed after electrospun 10PVA-5PP fibers compared to uncoated samples (Ra: 22.60 nm) with AFM analyzes.
Mutuk, Tuğba/0000-0003-0143-2721
Keywords: Ni-Ti Stent; PVA; Propolis; Electrospin; Nanofiber